It`s cold and there`s something to do: The changing geography of Canadian National Hockey League players` hometowns - Kaida, L.; Kitchen, P. (International Review for the Sociology of Sport, 2020)
Set within the framework of the birthplace effect literature and the seminal work of Curtis and Birch, this paper draws information from the publicly available database www.hockeydb.com and from the Census to examine the hometowns of Canadian National Hockey League (NHL) players from 1970 to 2015. It found that from a regional perspective, the distribution of players` hometowns remained fairly stable over the 46-year period with Ontario and the three Prairie provinces being prominent. Players from small centres have been well represented in the NHL. While larger urban areas have historically produced the most players, there has been a marked increase in `big city` players while the odds of making it are low. However, when the analysis is adjusted according to the population aged 10-19, boys growing up in small and mid-sized centres were at advantage in reaching the NHL until 2009. Finally, we discuss whether the growing presence of big city players in the NHL will affect the image of hockey as a national sport, as for many, small-town hockey remains at the heart of Canadian sporting culture.